Ascertaining patients' understandings of their condition: a conversation analysis of contradictory norms in cancer specialist consultations. Issue 3 (2nd September 2019) - Dew, Kevin; Barton, Josh; Stairmand, Jeannine; Sarfati, Diana; Signal, Louise
ABSTRACT: Patient-centred care requires patients to be active participants in decision-making in consultations. Decision-making participation requires patients to understand their condition and to be able to convey their health literacy to medical specialists they encounter. Based on conversation analysis of 18 audio-recorded consultations between cancer patients and a range of cancer care specialists, this article analyses the ways cancer specialists attempt to ascertain their patient's understanding of their disease. Cancer specialists routinely enquire about their patient's understanding. In doing so, they phrase enquiries in different ways, resulting in different patient responses. How questions are phrased can require patients to deal with contradictory norms in the consultation, such as the patient being competent but not assuming medical expertise, and potentially hinder patient participation. Alternatively, questions can allow patients to draw on their own experience and so facilitate greater patient involvement. Questions aimed directly at the patient's medical understanding result in minimal or negative responses. In contrast, questions directed at what the patient has been told or has experienced, elicit longer and more in-depth responses from the patient. This analysis illuminates the co-construction of cancer specialist consultations and suggests simple ways in which patient involvement in the consultation can be facilitated.